Comparing the wound healing potential of natural rubber latex serum and F1-protein: An in vivo approach - Morais, Pamela Cássia Rocha; Floriano, Juliana Ferreira [UNESP]; Garcia, Cristiane Garcia Paulino [UNESP]; Chagas, Ana Laura Destro [UNESP]; Mussagy, Cassamo Ussemane; Guerra, Nayrim Brizuela [UNESP]; Sant'Ana Pegorin Brasil, Giovana [UNESP]; Vicentine, Karina Ferrazzoli Devienne; Rocha, Lenaldo Branco; Oliveira, Carlo José Freire; Soares de Oliveira Junior, Robson Tadeu; Caetano, Guilherme Ferreira; et al. (Elsevier, 2024)
Chronic wounds pose significant health concerns. Current treatment options include natural compounds like natural rubber latex (NRL) from Hevea brasiliensis. NRL, particularly the F1 protein fraction, has demonstrated bioactivity, biocompatibility, and angiogenic effects. So far, there is no study comparing F1 protein with total NRL serum, and the necessity of downstream processing remains unknown. Here, we evaluated the angiogenic potential of F1 protein compared to total NRL serum and the need for downstream processing. For that, ion exchange chromatography (DEAE-Sepharose), antioxidant activity, physicochemical characterization, cell culture in McCoy fibroblasts, and wound healing in Balb-C mice were performed. Also, the evaluation of histology and collagen content and the levels of inflammatory mediators were quantified. McCoy fibroblast cell assay showed that F1 protein (0.01 %) and total NRL serum (0.01 %) significantly increased cell proliferation by 47.1 ± 11.3 % and 25.5 ± 2.5 %, respectively. However, the AA of F1 protein (78.9 ± 0.8 %) did not show a significant difference compared to NRL serum (77.0 ± 1.1 %). F1 protein and NRL serum were more effective in wound management in rodents. Histopathological analysis confirmed accelerated healing and advanced tissue repair. Similarly, the F1 protein (0.01 %) increased collagen, showing that this fraction can stimulate the synthesis of collagen by fibroblastic cells. Regarding cytokines production (IL-10, TNF-α, IFN-γ), F1 protein and NRL serum did not exert an impact on the synthesis of these cytokines. Furthermore, we did not observe statistically significant changes in dosages of enzymes (MPO and EPO) among the groups. Nevertheless, Nitric Oxide dosage was reduced drastically when the F1 protein (0.01 %) protein was applied topically. These findings contribute to the understanding of F1 protein and NRL serum properties and provide insights into cost-effectiveness and practical applications in medicine and biotechnology. Therefore, further research is needed to assess the economic feasibility of downstream processing for NRL-based herbal medicine derived from Hevea brasiliensis.
Keywords: Angiogenic potential; Chronic wounds; Downstream processing; F1 protein; Natural rubber latex